2018
DOI: 10.1111/bjh.15033
|View full text |Cite
|
Sign up to set email alerts
|

Unique anti‐myeloma activity by thiazolidine‐2,4‐dione compounds with Pim inhibiting activity

Abstract: Proviral Integrations of Moloney virus 2 (PIM2) is overexpressed in multiple myeloma (MM) cells, and regarded as an important therapeutic target. Here, we aimed to validate the therapeutic efficacy of different types of PIM inhibitors against MM cells for their possible clinical application. Intriguingly, the thiazolidine-2,4-dione-family compounds SMI-16a and SMI-4a reduced PIM2 protein levels and impaired MM cell survival preferentially in acidic conditions, in contrast to other types of PIM inhibitors, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…Multiple myeloma (MM), characterized by an abnormal increase in monoclonal paraprotein and the accumulation of cancerous plasma cells, is a progressive and debilitating malignancy 39 . Research has shown that PIM2 kinase is overexpressed in MM cells, and that the kinase inhibitors SMI-16a and SMI-4a can both reduce its kinase activity in MM cells 40 . PIM2 expression has also been shown to be up-regulated in bone marrow stromal cells, acting as a negative regulator for osteoblastogenesis, and PIM2 inhibition suppressed MM tumor progression and prevented bone destruction in vivo 41 .…”
Section: Pim2 Functions In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple myeloma (MM), characterized by an abnormal increase in monoclonal paraprotein and the accumulation of cancerous plasma cells, is a progressive and debilitating malignancy 39 . Research has shown that PIM2 kinase is overexpressed in MM cells, and that the kinase inhibitors SMI-16a and SMI-4a can both reduce its kinase activity in MM cells 40 . PIM2 expression has also been shown to be up-regulated in bone marrow stromal cells, acting as a negative regulator for osteoblastogenesis, and PIM2 inhibition suppressed MM tumor progression and prevented bone destruction in vivo 41 .…”
Section: Pim2 Functions In Cancermentioning
confidence: 99%
“…SMI-16a has been shown to destroy clone formation in MM cells, and their tumorigenic ability in vivo under acidic conditions, which restores the anti-MM effects of Dox. The accumulation of PIM2 in MM cells can be reduced using proteasome inhibitors, and SMI-16a has been shown to enhance the cytotoxic effects of carfilzomib by inhibiting the accumulation of PIM2 by proteasome inhibitors 40 . PIM2 has also been shown to act as a negative regulator for osteoblastogenesis.…”
Section: The Value Of Treatments With Pim2 Inhibitormentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to SMI-4a, SMI-16a reduces the capacities of colony formation of MM cells and their tumorigenic activity in vivo under acidic conditions, and restores the anti-MM effects of Doxorubicin [ 74 ]. Additionally, SMI-16a was also shown to increase the cytotoxic effects of carfilzomib by inhibiting the PIM2 accumulation [ 84 ].…”
Section: Pim Kinase Inhibitorsmentioning
confidence: 99%
“…Although its role in the B‐cell differentiation process is not well understood, FKBP11 was not only found as a putative target of IRF4 initiating the pre‐PB stage [44] but also increased in lupus B cells inducing B‐cell tolerance breakdown [45]. Additionally, we underlined proteins involving in cell survival that may be valuable targets for controlling lymphoid neoplastic disorders such as PIM2 , TRIB1 , SEL1L and ELL2 [46,47]. On the other hand, the human PB signature encompassed 283 genes mostly involved in cell activation (Figure C,D).…”
Section: Resultsmentioning
confidence: 99%